The ERG-regulated LINC00920 promotes prostate cancer cell survival via the 14-3-3ε-FOXO pathway - Angeles, Arlou Kristina J.; Heckmann, Doreen; Flosdorf, Niclas; Duensing, Stefan; Sültmann, Holger (Molecular cancer research, 2020)
Numerous noncoding transcripts have been reported to correlate with cancer development and progression. Nevertheless, there remains a paucity of long noncoding RNAs (lncRNA) with well-elucidated functional roles. Here, we leverage the International Cancer Genome Consortium-Early Onset Prostate Cancer transcriptome and identify the previously uncharacterized lncRNA LINC00920 to be upregulated in prostate tumors. Phenotypic characterization of LINC00920 revealed its positive impact on cellular proliferation, colony formation, and migration. We demonstrate that LINC00920 transcription is directly activated by ERG, an oncogenic transcription factor overexpressed in 50% of prostate cancers. Chromatin isolation by RNA purification-mass spectrometry revealed the interaction of LINC00920 with the 14-3-3ε protein, leading to enhanced sequestration of tumor suppressive FOXO1. Altogether, our results provide a rationale on how ERG overexpression, partly by driving LINC00920 transcription, could confer survival advantage to prostate cancer cells and potentially prime PTEN-intact prostate cells for cellular transformation through FOXO inactivation. - Implications: The study describes a novel lncRNA-mediated mechanism of regulating the FOXO signaling pathway and provides additional insight into the role of ERG in prostate cancer cells.